Risk Factors of First Febrile Seizures Admitted in a Tertiary Care Hospital - Nahid, Fauzia; Rahman, Farhana; Hoque, Md Mahbubul; Amin, Md Ruhul; Yasmin, Tahmina; Ara, Rawshan (Ibrahim Cardiac Medical Journal, 2018)
Background & objective: Febrile seizure (FS) is the most common convulsive event in children. It is the most common type of seizure that every pediatrician has to deal with. However, the etiology of febrile seizure is still unclear. The present study was intended to identify the risk factors of first febrile convulsion among 6 months to 5 years old children. Materials & Methods: A case-control study was carried out on a total of 200 children-100 cases (children with febrile convulsion) & 100 controls (without febrile convulsion) selected from the In-patient Department of Dhaka Shishu Hospital over a period of six months between May 2012 to October 2012. Data were collected on variables of interest using a semi-structured research instrument. The Chi-square test and Odd Ratio were employed to compare the risk factors between case and control groups. Result: There was no association of febrile seizure with age of the children, but males were more often associated with FS than the females with risk of developing febrile seizures in boys was 3.5-fold (95% CI=1.8 -6.8) higher than that in girls (p<0.001). The risk of having FS in children with prematurity and caesarean delivery was 2.8 times (95% CI=1.5-5.0) and 2-times (95% CI=1.4-2.6) greater than those in children without having these conditions (p=0.001 and p<0.001 respectively). The children with family history of febrile seizure tends to be associated with first febrile seizures and the odds of having the condition is 36.4 (95% CI=15.4-85.7). There was no significant relationship between family history of epilepsy and first febrile seizure (p=0.061). The children with shorter duration of breast feeding (6-12 months) carry 2.9(95% CI=2.0-4.0) times higher risk of having first febrile seizure than those with longer duration of breast-feeding (p<0.001). Exclusively breast-fed children were less susceptible to develop febrile seizures (OR=0.149, 95% CI: 0.08-0.23). Twelve cases developed perinatal asphyxia as opposed to only 2 of the control group and the risk of having FS in children with perinatal asphyxia was 1.8(95% CI=1.4-2.3) times higher than those without having the history ofperinatal asphyxia (p<0.001). Three-quarters of the children presented with FS had viral fever whereas only 4% of the controls had viral fever indicating that viral fever triggers the development of FS much more frequently than any other childhood illness (p<0.001). Conclusion: The study concluded that male sex, preterm baby, positive family history of febrile seizures, less than 6 months of exclusive breast feeding, not continuing the breast-feeding beyond 12 months, perinatal asphyxia and viral infections are the predictors of first febrile seizure. Preventive measures in removing these risk factors can go a long way to a decrease the incidence of febrile seizures. Ibrahim Card Med J 2016; 6 (1&2): 56-61